Success of Library awareness programmes in the Faculty of Science, University of Colombo - Somaratna, Sajeewanie D. (My University, 2010)
The usage of Library resources by staff and students of the faculty was in a low level and the reason was identified as unawareness of available resources and services in the library. A malfunctioning information flow from the library to its users was identified as the main drawback for this low awareness level. The first step in upgrading the library awareness level of users was the improvement of important promotion tools, basic infrastructure facilities and the adoption of important strategies. As the next step the information flowing pathways from the Library to students were cleared. Due to low contacts between the Library and the students, the academic staff members were identified as intermediates to influence students to use library resources. The 1st workshop was organized for the academic staff members jointly by the Library and the Library committee Faculty of Science. Very successful user awareness program for third year and fourth year Special degree students and also for general degree students was conducted as the 2nd step. The awareness level of users was measured before and at the end of the sessions using a five point Likert scale. The progress gap was identified for selected ten items; Library automation, Library catalogue, Library classification scheme, Printed collection, E ? resources, Inter Library Loans, Document delivery service, User education programs, Library networks and Library web site. The largest awareness gap was identified for Inter Library loans followed by user education programs, library web site and library networks. After the library awareness programs the utilization of library resources and services improved dramatically and the most important achievement gained from the project to accept a credit base enhancement course from the library for undergraduates of the Faculty of Science.